LEGAL REGULATION IN THE LIGHT OF TRADITIONS AND INNOVATIONS (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This article is devoted to modern problems of legal regulation. In domestic legal science, attempts are being made to significantly revise approaches not only to a relatively independent problem, namely legal regulation, but also to the role of law in general. Of course, technology significantly influences on the legal environment, which is increasingly becoming digital. At the same time, the general principles and views fundamentally continue to remain the same. In this regard, the problem of compatibility of traditional approaches to legal regulation and the need to make adjustments to established theoretical and practical guidelines has emerged, preserving, if possible, those provisions that can be considered to some extent fundamental.
Keywords: state; law; regulation; technology; digitalization